Water, water, everywhere: Using silent accounting to examine accountability for a desalination project. Issue 1 (6th March 2017) - McDonald-Kerr, Lachlan
Abstract : Purpose: This paper aims to examine how social and environmental issues were accounted for and traded off within decision-making for Australia's largest seawater desalination plant. This is done through an investigation of disclosures contained within key publicly available documents pertaining to the project. Design/methodology/approach: The study deploys content analysis to initially identify relevant disclosures. Themes and subthemes are based on definitions of social and environmental accounting adapted from prior research. Relevant information was used to develop "silent accounts" to identify and analyse accountability issues in the case. Findings: It was found that a number of claims made throughout reporting were unsupported or insufficiently explained. At the same time, it is found that various forms of basic measurements used to describe social and environmental issues conveyed the rationale of decision makers. It is concluded that many of the claims were asserted rather than evidenced; yet, the manner and context of their presentation gave them the appearance of being incontestable truths. Further, it is argued that the portrayal of social and environmental issues through measurable means is emblematic of values associated with contemporary neoliberal and public sector reforms. Research limitations/implications: The findings and conclusions of this study are contextually bound and therefore limited to this case. Practical implications: This paper illustrates problems with the reporting of non-financial information and strengthens our understanding of the use of "silent accounting". It illustrates the value of this approach to research examining accounting and accountability issues. Originality/value: The findings contribute to the literature on social and environmental accounting by providing unique empirical analysis of non-financial disclosures within publicly available reporting.